Eateries and eating outside of home in Maribor - Drozg, Vlado (Journal for Geography, 2024)
The paper deals with eateries and eating habits among guests of some restaurants in Maribor. Eating outside the home is increasingly associated with leisure time, entertainment, and socializing in economically developed societies. The characteristics of eateries in Maribor, like type, allocation in the city area, structure and changes over past 20 years are interpreted in the context of general social conditions and responses about food consumption habits of eateries’ guests. Data on the structure of eateries and eating habits were obtained through observation and unstructured interviews with employees and randomly selected guests. The number of eateries has increased, especially those serving fast food and foreign cuisine.